How to assess risk before cardiac surgery. A challenge not only for the cardiac surgeon, anaesthetist and cardiologist but also for the general practitioner - Szafron, Bartłomiej; Szafranek, Andrzej; Zembala, Marian (Przewodnik Lekarza/Guide for GPs, 2008)
General practitioners more and more frequently have to treat patients qualified for cardiac surgery. Operative risk estimation is an essential part of this process. Risk models can offer real support in mortality prediction. EuroSCORE plays an outstanding role here, due to the way it was derived and its widespread use in European cardiac surgery. Despite significant differences between populations in terms of risk factor levels it was positively validated in the setting of the Polish cardiac surgery centre. EuroSCORE variables are discussed including their levels and impact on outcome of surgery. Being aware of the danger associated with risk factors allows for optimal preparation for surgery and results in risk reduction.